1984
DOI: 10.1007/bf00115344
|View full text |Cite
|
Sign up to set email alerts
|

Cladistical analysis of primitive G-band sequences for the karyotype of the ancestor of the Cricetidae complex of rodents

Abstract: Homologous segments identified by G-banding sequences of chromosomes of Peromyscus boylii, Neotoma micropus, Oryzomys capito, (Family Cricetidae) Rattus norvegicus, Melomys burtonL and Apodemus sylvaticus (Family Muridae) were used to hypothesize a chromosomal condition for the cricetid ancestor. A critical assumption in proposing the primitive G-banding sequences for a given chromosome is that if the outgroup and ingroup taxa have a specific sequence, then the ancestor of the ingroup taxa also had that same s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
3

Year Published

1984
1984
1989
1989

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
1
26
0
3
Order By: Relevance
“…These systematic assumptions are consistent with some classification schemes (Hooper and Musser, 1964;Hershkovitz, 1966Hershkovitz, , 1972Reig, 1977) and allow the determination of primitive and derived G-band seq.uences at several points in the chromosomal evolution of Neotropical cricetines examined. The primitive chromosomal complement (14 largest pairs) for the Cricetidae was determined by Koop et al (1984a) to be like that found in Neotoma micropus. In this study we have analyzed characters of the South American taxa relative to that of N. micropus in order to determine polarity in transition series.…”
Section: Methodsmentioning
confidence: 65%
See 4 more Smart Citations
“…These systematic assumptions are consistent with some classification schemes (Hooper and Musser, 1964;Hershkovitz, 1966Hershkovitz, , 1972Reig, 1977) and allow the determination of primitive and derived G-band seq.uences at several points in the chromosomal evolution of Neotropical cricetines examined. The primitive chromosomal complement (14 largest pairs) for the Cricetidae was determined by Koop et al (1984a) to be like that found in Neotoma micropus. In this study we have analyzed characters of the South American taxa relative to that of N. micropus in order to determine polarity in transition series.…”
Section: Methodsmentioning
confidence: 65%
“…In chromosome 9, the proposed ancestral G-band sequence (Koop et al, 1984a) was found in Neotoma micropus, S. hispidus, Nectomys squamipes, H. brasiliensis, 0. capito, 0. palustris, 0. couesi, and 0. caliginosus. Oryzomys sp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations